Cell and protein compatible 3D bioprinting of mechanically strong constructs for bone repair. (2nd July 2015) - Sawkins, M J; Mistry, P; Brown, B N; Shakesheff, K M; Bonassar, L J; Yang, J
Abstract: Rapid prototyping of bone tissue engineering constructs often utilizes elevated temperatures, organic solvents and/or UV light for materials processing. These harsh conditions may prevent the incorporation of cells and therapeutic proteins in the fabrication processes. Here we developed a method for using bioprinting to produce constructs from a thermoresponsive microparticulate material based on poly(lactic-co-glycolic acid) at ambient conditions. These constructs could be engineered with yield stresses of up to 1.22 MPa and Young's moduli of up to 57.3 MPa which are within the range of properties of human cancellous bone. Further study showed that protein-releasing microspheres could be incorporated into the bioprinted constructs. The release of the model protein lysozyme from bioprinted constructs was sustainted for a period of 15 days and a high degree of protein activity could be measured up to day 9. This work suggests that bioprinting is a viable route to the production of mechanically strong constructs for bone repair under mild conditions which allow the inclusion of viable cells and active proteins.